2016
DOI: 10.1021/acs.analchem.6b02007
|View full text |Cite
|
Sign up to set email alerts
|

Effect-Directed Discovery of Bioactive Compounds Followed by Highly Targeted Characterization, Isolation and Identification, Exemplarily Shown for Solidago virgaurea

Abstract: A nontargeted, effect-directed screening (bioprofiling) and a subsequent highly targeted characterization of antibacterial compounds from plant matrices is demonstrated on the example of Solidago virgaurea root extracts. The procedure comprises high-performance thin-layer chromatography (HPTLC) coupled with six bacterial bioassays including two plant pathogens, a radical scavenging assay, an acetylcholinesterase assay as well as in situ and ex situ mass spectrometric analyses. In situ mass spectra were directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Even though the overall composition is based on the same components, quantitative and to some extent qualitative differences raise doubts about their full equivalence. [17] Antioxidant capacity of crude drugs is highly related to the phenolic content which is generally more soluble in polar organic solvents than in water. Hyperosidea European Pharmacopoeia standard for calculation of flavonoid content in Solidaginis herba was absent from all analyzed samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the overall composition is based on the same components, quantitative and to some extent qualitative differences raise doubts about their full equivalence. [17] Antioxidant capacity of crude drugs is highly related to the phenolic content which is generally more soluble in polar organic solvents than in water. Hyperosidea European Pharmacopoeia standard for calculation of flavonoid content in Solidaginis herba was absent from all analyzed samples.…”
Section: Discussionmentioning
confidence: 99%
“…The information on the phytochemical composition of underground parts of Solidago species is scarce, except for the report on bioassay-guided isolation of the main antimicrobial polyacetylenes such as (2Z,8Z)and (2E,8Z)-matricaria esters from S. virgaurea root and shoot. [17] Antioxidant capacity of crude drugs is highly related to the phenolic content which is generally more soluble in polar organic solvents than in water.…”
Section: Discussionmentioning
confidence: 99%
“…virgaurea has a diversity of medicinal uses in the territories where it is spread. Probably its most widely known ethnopharmacological uses are related to kidney disorders (being often found in teas intended to help passing kidney calculi), urinary tract infections, the overactive bladder syndrome, and prostatic diseases [30][31][32], the urologic uses of the plant going back at least to the writings of Arnold von Villanova (1240-1311) [33]. Traditionally, the aerial parts of the plant have been used for healing and antiseptic properties [9], as well as for the treatment of diabetes, allergies, and gastro-intestinal disorders [8,32].…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…The bioactivity-guided approaches are emerging in the field of natural product discovery [112], in which NMR can also facilitate the identification of the bioactive compounds by pattern recognition strategy. Abedini et al [90] reported the use of 13 C NMR dereplication method for the unambiguous identification of oregonin, hirsutanonol, and alusenon 1a in the methanol extract of A. glutinosa bark.…”
Section: Nuclear Magnetic Resonance (Nmr) Spectroscopymentioning
confidence: 99%